1991
DOI: 10.1159/000181893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>L</i>-Asparaginase on Insulin Secretion from Isolated Rat Islets of Langerhans

Abstract: The effects of L-asparaginase were evaluated on glucose-induced insulin release from isolated rat islets of Langerhans. Islets were obtained by enzymatic digestion of pancreas from Sprague-Dawley rats. The study of L-asparaginase effects on insulin secretion was performed in a static incubation of islets. Insulin secretion was measured at 60 min of incubation with different secretagogues with and without L-asparaginase. L-Asparaginase at concentrations from 310 to 5,000 U/ml could inhibit the glucose-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…(15, 22) At higher concentrations in vitro , asparaginase has been demonstrated to cause irreversible alteration of asparagine in the cells and/or islet cell death. (25, 26) Based on these mechanisms, prolonged abnormalities of glucose metabolism, manifested as hyperglycemia and hypoinsulinemia would be expected in patients who have received asparaginase therapy. Mohn et al previously studied ALL survivors and found decreased insulin secretion in glucose tolerance testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(15, 22) At higher concentrations in vitro , asparaginase has been demonstrated to cause irreversible alteration of asparagine in the cells and/or islet cell death. (25, 26) Based on these mechanisms, prolonged abnormalities of glucose metabolism, manifested as hyperglycemia and hypoinsulinemia would be expected in patients who have received asparaginase therapy. Mohn et al previously studied ALL survivors and found decreased insulin secretion in glucose tolerance testing.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperglycemic effect of asparaginase results from a dose‐dependent decrease in insulin secretion from pancreatic islet cells 15, 22. At higher concentrations in vitro, asparaginase has been demonstrated to cause irreversible alteration of asparagine in the cells and/or islet cell death 25, 26. Based on these mechanisms, prolonged abnormalities of glucose metabolism, manifested as hyperglycemia and hypoinsulinemia would be expected in patients who have received asparaginase therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, glucose stimulated insulin secretion is often tested with glucose in combination with chemicals like IBMX and theophylline (Christie et al 1984, Draznin et al 1985, Pou et al 1991, Omer et al 2003. IBMX is a phosphodiesterase inhibitor that elevates intracellular cAMP, which increases the release of free Ca 2+ and consequently the release of insulin (Siegel et al 1980, Gerber et al 1981, Valverde et al 1983.…”
mentioning
confidence: 99%
“…The effects of chemotherapy on glucose levels is assigned, at least in part, to the effects of corticosteroids (either prednisone or dexamethasone) and asparaginase. The first, by increasing glycogenolysis and gluconeogenesis and, the second, by reducting insulin secretion (via inhibition of cAMP levels) [ 30 , 31 ]. Previous work have identified age >10 years, female, obesity, family history of diabetes, and Down syndrome as risk factors for the development of transient hyperglycaemia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%